Consumer Perceptions of Global and Local Brands in the India Retail Sector - Bajaj, Smriti (2006)
Purpose The purpose of this dissertation is to investigate, in an emerging market, consumer attitudes towards local and foreign brand purchases against a background of factors like Culture, Country of Origin, Product quality and services. A comprehensive model broadens knowledge on consumer behaviour by incorporating the above mentioned factors. Design/methodology/approach- India is the emerging market studied. A total of 18 respondents were interviewed face-to-face using a semi structured questionnaire in the city of Mumbai and Indian students studying in the United Kingdom. Findings- It was found that the quality of global brands was perceived to be generally higher and superior to local brands. Most consumers also associated greater accessibility of foreign brands in the Indian market with better quality at lower prices. Indian consumers were not prejudiced against foreign brand names. In fact, they evaluated them higher on technology, quality, status and esteem than Indian brands and attributed higher credibility to those countries of origin. Research Limitations/implications- This study adds to the body of knowledge about consumer behaviour and their perceptions of global vs. local brands, in a massive and fast developing market. Managerial Implications- As companies become global, managers must possess a thorough understanding of the attitudinal and behavioural characteristics of emerging consumer markets, because what is known about consumers in one part of the world is not applicable to consumers in other parts. Key words- Global Brands, India, Culture, Country of Origin and Product and Service Quality, Materialism.